IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATAN MUTU PENDIDIKAN DI SMA NEGERI 1 WATUBANGGA KABUPATEN KOLAKA - Soharab, Vivi Zulfianti (MAP (Jurnal Manajemen dan Administrasi Publik), 2024)
School-based management is a form of education reform agenda in Indonesia which is a necessity to empower the role of schools and communities in supporting the management and implementation of education in schools. Essentially School-Based Management offers discourse when schools appear relatively autonomous, by not reducing the role of government, especially in funding.This study aims to determine how the application of school-based management in improving the quality of education in SMA 1 Watubangga District. Kolaka referred to supporting factors and inhibitors, as well as efforts made to overcome the obstacles faced. This research is classified as a qualitative descriptive study. The informants in this study were the Principal, Deputy Principal, Board of Teachers, Students, School Committees and parents of students. Methods of documentation data collection and interviews.The results obtained from the study provide an overview of the application of school-based management in improving the quality of education in Watubangga 1 Public High School as well as various factors that support and hinder the process of implementing school-based management in improving the quality of education and efforts to overcome the obstacles faced.